TD-LTE and TD-SCDMA Collaborative Network Optimizing Strategy - Chang Li; Jianbin Zhang; Jing An (Dianxin kexue)
Compared to traditional network，the network structure has a greater impact on the quality of TD-LTE network.If only upgrade directly in the original site based on TD-SCDMA，the original structure and quality issues would be inherited.On the basis of the problems encountered in the shared antenna collaborative optimization，a collaborative network optimization method was presented.Network problems of TD-SCDMA and TD-LTE were solved from the dimensions of network structure，coverage and interference by using project parameters，measurement report，frequency sweep test，driving test and other data.After that，by using network planning and optimization tools，collaborative optimization scheme was outputted and verified in the existing network to solve these problems.Finally，TD-SCDMA and TD-LTE collaborative optimization adjustment strategy was summed up by evaluating implementation effects.